Pengembangan Media Pembelajaran Fisika berbasis Adobe Flash Professional CS6 Untuk Mata Kuliah Fisika Dasar I - Boby Syefrinando; Suraida Suraida; Af Parman (Department of Physics Education, Universitas Mataram, 2020)
The aim of this research is to develop learning media based on adobe flash professional CS6 on the subject of mechanics (kinematics and dynamics). In this research produced a product in which several questionnaires were distributed to several experts: media experts, concept experts, linguists, lecturers and students, to find out the validity, practicality and effectiveness of learning media. The research method uses the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). The results of this study found that the learning media has good indicators. This is evidenced by the results of data analysis obtained from respondents. Based on the assessment of media experts, concept experts and language experts learning media are categorized as very valid, with an average percentage of 91.25% by media experts, 92% by concept experts and 100% by language experts. The practicality of the media obtained 91% of the responses of lecturers, 84% of students with very practical criteria. The effectiveness of the media obtained from an increase in student learning outcomes by 0.8% with high improvement criteria. From the results of the data obtained, this learning media have valid criteria according to experts, practical, and effective and can be used by lecturers and student.